2021
DOI: 10.3390/diagnostics11050847
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the Noise Penalty Factor on Quantification in Bayesian Penalized Likelihood (Q.Clear) Reconstructions of 68Ga-PSMA PET/CT Scans

Abstract: Functional imaging with 68Ga prostate-specific membrane antigen (PSMA) and positron emission tomography (PET) can fulfill an important role in treatment selection and adjustment in prostate cancer. This article focusses on quantitative assessment of 68Ga-PSMA-PET. The effect of various parameters on standardized uptake values (SUVs) is explored, and an optimal Bayesian penalized likelihood (BPL) reconstruction is suggested. PET acquisitions of two phantoms consisting of a background compartment and spheres wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
1
16
0
3
Order By: Relevance
“…Similar studies have also reported better overall image quality by Q.Clear compared with OSEM in [ 68 Ga]Ga-DOTANOC PET/CT scans [ 29 ], 18 F-fluciclovine PET/CT scans [ 20 ], and [ 68 Ga]Ga-PSMA PET/CT scans [ 30 ]. This indicates that the improved image quality provided by Q.Clear is not exclusively dedicated to 2-[ 18 F]FDG-PET/CT scans.…”
Section: Discussionmentioning
confidence: 72%
“…Similar studies have also reported better overall image quality by Q.Clear compared with OSEM in [ 68 Ga]Ga-DOTANOC PET/CT scans [ 29 ], 18 F-fluciclovine PET/CT scans [ 20 ], and [ 68 Ga]Ga-PSMA PET/CT scans [ 30 ]. This indicates that the improved image quality provided by Q.Clear is not exclusively dedicated to 2-[ 18 F]FDG-PET/CT scans.…”
Section: Discussionmentioning
confidence: 72%
“…Generally, high image quality is essential to precise interpretation of PET/CT clinical studies. Bayesian penalized likelihood estimation reconstruction algorithm (BPL) has been developed and clinically implemented to improve image signal-to-noise ratio and lesion signal-to-background ratio compared to the widely used ordered subset expectation maximization (OSEM) for 68 Ga tracer PET [5] , which is partly accountable to the full iterative convergence of the BPL algorithm without excessive noise ampli cation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, high image quality is essential to the precise interpretation of PET/CT clinical studies. The Bayesian penalized likelihood (BPL) reconstruction algorithm has been developed and clinically implemented to improve the image signal-to-noise ratio and lesion signal-to-background ratio compared to the widely used ordered subset expectation maximization (OSEM) algorithm for 68 Ga tracers [ 5 ]; the superior performance of the BPL algorithm is due in part to its full iterative convergence without excessive noise amplification. Hence, the BPL algorithm has the potential to further improve quantitation accuracy [ 6 ], shorten acquisition time [ 7 ], and reduce the amount of radioactivity injected [ 8 ], while maintaining or even improving the image quality.…”
Section: Introductionmentioning
confidence: 99%